2012
DOI: 10.1016/j.exer.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Composition and proteolytic processing of corneal deposits associated with mutations in the TGFBI gene

Abstract: Different types of granular corneal dystrophy (GCD)1 and lattice corneal dystrophy (LCD) are associated with mutations in the transforming growth factor beta induced gene (TGFBI). These dystrophies are characterized by the formation of non-amyloid granular deposits (GCDs) and amyloid (LCD type 1 and its variants) in the cornea. Typical corneal non-amyloid deposits from GCD type 2 (R124H), amyloid from a variant of LCD type 1 (V624M) and disease-free tissue controls were procured by laser capture microdissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(101 citation statements)
references
References 28 publications
11
90
0
Order By: Relevance
“…In line with this hypothesis, accumulation of A␤ was observed in astrocytoma cell culture supernatants following chemical inhibition of HTRA1 and by co-localization of HTRA1 with ␤-amyloid deposits in human brain samples (24). The recently reported association of HTRA1 with corneal amyloid deposits of TGFBI (transforming growth factor ␤-induced gene), however, raises both the possibility of the generation of amyloidogenic fragments and the clearance of amyloid aggregates through proteolysis by HTRA1 (54). Moreover, recent evidence from studying adult macular degeneration suggests that it is the increased activity of HTRA1, resulting from its overexpression that causes disease symptoms (12,13).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In line with this hypothesis, accumulation of A␤ was observed in astrocytoma cell culture supernatants following chemical inhibition of HTRA1 and by co-localization of HTRA1 with ␤-amyloid deposits in human brain samples (24). The recently reported association of HTRA1 with corneal amyloid deposits of TGFBI (transforming growth factor ␤-induced gene), however, raises both the possibility of the generation of amyloidogenic fragments and the clearance of amyloid aggregates through proteolysis by HTRA1 (54). Moreover, recent evidence from studying adult macular degeneration suggests that it is the increased activity of HTRA1, resulting from its overexpression that causes disease symptoms (12,13).…”
Section: Discussionmentioning
confidence: 55%
“…A recent study showed the association of HTRA1 with amyloid deposits in the human cornea (54). Accordingly, the observations that HTRA1 degrades aggregated tau as well as A␤ pep- tides (24), its up-regulation on the transcriptional level and the activation of its proteolytic activity in response to the presence of elevated tau concentrations, respectively, suggest that the protein quality control function of HtrA proteases is conserved.…”
Section: Discussionmentioning
confidence: 97%
“…This has been suggested to be linked to the slow turnover of proteins in the cornea due to a lack of blood vessels (22). Furthermore, a C-terminal fragment of TGFBIp derived from FAS1-4 has been found to accumulate in amyloids of the mutant V624M, forming lattice-type deposits in the cornea (23). The molecular events leading to protein aggregation and accumulation involved in corneal dystrophy are still unclear.…”
Section: Transforming Growth Factor ␤ Induced Protein (Tgfbip)mentioning
confidence: 99%
“…The deposits are localized to various layers of the cornea depending on the gene involved and its specific mutation, and they affect corneal transparency and visual acuity. CLU has been found colocalized in deposits of two types of superficial and stromal corneal dystrophies: the TGFBIlinked corneal dystrophies [105,106] and the lattice type I corneal dystrophy linked to mutations in the gene for TACSTD2 (Tumor-Associated Calcium Signal Transducer 2) [107]. In addition, CLU is markedly elevated in Fuchs' Endothelial Corneal Dystrophy (FECD), the most common cause of corneal endothelial dysfunction [108][109][110].…”
Section: Corneal Dystrophies -This Is a Group Of Inherited Disorders mentioning
confidence: 99%